A buddhist approach to suicide prevention - Chamlong Disayavanish (2018)
The majority of the Thai population is Buddhists and Buddhism has a great deal of influence on their mind, character, way of life, and health, particularly mental health. According to the Four Noble Truths (Cattāri ariyasaccani), suicide is a form of suffering that is originated from craving (Tan dot below hā). Therefore, human beings cannot avoid suffering by taking their own lives, nor do they escape from "the wheel of suffering" by doing so. Moreover, the consequence of suicide is a rebirth in the woeful planes of existence, and hence further suffering endlessly. From the present study, the Buddhist approach to suicide prevention can be considered in the following areas: 1) Buddhist attitude toward suicide, 2) faith and confidence in life after death, 3) providing monks with general knowledge and understanding about suicide and life after death, 4) early identification of mental disorders, persons at risk of suicide and prompt referral to appropriate mental health professionals, 5) control of access to instruments of suicide, 6) control of alcohol and drug abuse, 7) prevention of HIV infection, 8) responsible media reporting and 9) practice of meditation.